The Augmented Spherical Wave Method A Comprehensive Treatment - Eyert, Volker; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The Augmented Spherical Wave (ASW) method is one of the most powerful approaches for handling the requirements of finite basis sets in DFT calculations. While it is particularly suited for the calculation of the electronic, magnetic, and optical properties of solid-state materials, recent developments allow application, in addition, to the elastic properties and phonon spectra. The book addresses all those who want to learn about methods for electronic structure calculations and the ASW method, in particular.
Introduction -- The Standard ASW Method -- Envelope Functions and Structure Constants -- The Plane-Wave Based Full-Potential ASW Method -- Details of the Standard ASW Method -- Details of the Envelope Functions -- Details of the Plane-Wave Based Full-Potential ASW Method -- Brillouin Integration -- Index.
Keywords: Condensed matter; Physics; Chemistry, Physical and theoretical; Condensed Matter Physics; Numerical and Computational Physics, Simulation; Theoretical and Computational Chemistry